THINKING ULUMUL QUR'AN KH. MUNTAHA AL-HAFIDZ, A STUDY TAHQIQI/PHILOLOGICAL AND CONTENT ANALYSIS OF THE BOOK ABHAR AL-QUR'AN - Muhtadin, Khoirul; Mukrimun, Amin; Nurcholisho, Lilik Rochmad; Fawwaz, M (Universitas Muhammadiyah Surakarta, 2023)
Ulumul Qur'an is one of the basic knowledge of Islam which has many branches. It discusses issues that are ushuli and furu'i, among the science of ushuli are makki-madani, asbabun nuzul, nasikh-mansukh, muhkam-mutasyabih and the others. The furu'i examples include adab or ethics and fadha'ilul Qur'an. This furu'i discussion is useful because there is a term for the science of perfection (kamalat) in Islam. A Qur'anic scholar from Wonosobo, KH. Muntaha Al-Hafidz has special attention in this knowledge of kamalat or perfection. He wrote a book